138 Analytical Methods for Organometallic Chelation Testing. (30th November 2020) - Walker, Edward
Abstract: Chelated minerals have increasingly captured the attention of scientists, manufacturers, and consumers in nutritional markets during the past five decades, due to their enhanced bioavailability compared to traditional ionic metal compounds. A wide variety of organic ligands bind to metal ions to form complexes that are generally referred to as chelates, including amino acids, peptides, proteins and carboxylic acids. Chemical reactions used to synthesize mineral chelates are affected by a number of factors that can alter the extent of chelation in manufactured products, such as pH, temperature, concentration, solvation, competing ions and ligands, and other variables. Qualitative and quantitative determination of chelation can be a daunting challenge, especially for dilute micronutrient minerals in complex matrices. Measuring chelation between metals and their ligands specifically focuses on the attractive forces between them. Analytical methods to determine the extent of chelation rely on a wide array of spectroscopic and electrochemical techniques. Very few standard methods of analysis exist to quantitatively measure the extent of chelation in nutritional products. A variety of these methods will be reviewed and compared for their potential use as standard methods of analysis.